A Critique on the Book Organizational Change (Themes & Issues) - Gholamreza Goodarzi; Mansooreh Moeini Korbekandi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Organizations are one of the main foundations of today’s society, and management is the most important factor in the life, growth, and development or death of organizations. The manager guides the process from the current situation to the desired situation and strives at every moment to create a better future. The past has happened with all its nature and learning, and with all the impact it can have on the future, and no human force can recreate it in a different way, but the future is on its way and an important part of it has to do with what is happening today. This article examines and critiques the book Organizational Change (Themes & Issues) by Jim Grieves, translated by Dr. Parviz Ahmadi and first the book is evaluated in terms of form and then it is considered in terms of content and structure. Also, the book’s expandable points are mentioned to make it richer.